Impact of Glycemic Status on Oncological Emergencies In A Tertiary Care Hospital In Bangladesh: A Preliminary Study - Rahman, Md Raziur; Sarker, Rene Suzan Claude; Afroze, Samira Rahat; Rahim, Muhammad Abdur; Uddin, Khwaja Nazim (Bangladesh Critical Care Journal, 2016)
Background : Dealing oncologic emergencies are challenging tasks for any concerned physician. The task becomes even more challenging if the scenario is complicated with diabetes and vice-versa. The burden of non-communicable diseases such as cancer and diabetes is also increasing throughout the world resulting in increasing morbidity and mortality. To the best of our knowledge, this is the first study in Bangladesh emphasizing on patients presenting with oncologic emergencies where relation to their glycemic status has also been analyzed. Methods : This cross sectional, observational study was carried out from January 2011 to June 2016. Adult patients of either sex admitted in Internal Medicine Department of BIRDEM (Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders) General Hospital diagnosed with malignancy irrespective of their diabetic status were purposively and consecutively included in this study. Out of 114 such cases 23 patients had oncologic emergencies. Different variables of these 23 cases of oncologic emergencies were analyzed with co-relation to diabetic status, such as age, gender, demography, co-morbid conditions, clinical features, type of malignancy and treatment outcome. Results : Eight different kinds of oncologic emergencies were observed among 11 different categories of malignancies. Only 23 oncologic emergency cases were identified among 114 cancer patients. The common emergencies were marrow failure (26.1%), Neutropenic sepsis (21.74%) and hypercalcemia (17.39%). The common malignancies were leukaemia (17.39%), carcinoma lung (13.04%), pancreatic carcinoma (13.04%) and multiple metastasis (13.04%). Two-third of the patients were male (69.57%) and nearly half of the patients aged above 60 years (43.5%). More than half of the patients came from urban background (52.2%). Two-third of the patients were diabetic (73.91%). It was observed that there were 10 cases (43.48%) with more than one co-morbid conditions and all of them belonged to the diabetic group. Those who had no co-morbidities (26.09%) were all non-diabetic (p<0.05). Six cases (26.09%) had more than one clinical features during the critical phase. Out of them 5 were diabetic (21.74%). Most common presenting feature was neurological (17.39%) followed by anaemia (13.04%), lymphadenopathy (8.7%), anorexia (8.7%) and pain (8.7%). Among these 23 cases only 3 (13.04%) patients recovered from oncologic emergency to baseline status. The condition of 4 patients (17.39%) remained static without further improvement and 4 patients (17.39%) deteriorated. It is to mention that in the diabetic group recovery rate from oncologic emergencies were less and non-responder /deterioration /death / lost from follow up cases were comparatively more. Unfortunately there were 3 cases of death and 9 patients denied further treatment or were lost from follow up. Conclusion : In this study we conclude that oncological emergencies and co-morbidities were found more frequently in the diabetic group than the non-diabetic counterpart. Since this is a preliminary study, further studies in different institutes should be encouraged in this field to gather more evidence to support our observation. Bangladesh Crit Care J September 2016; 4 (2): 96-99